KARO LANGUAGE MAINETANCE IN TIGA JUHAR - Vivi Novalia Sitinjak; Elita Modesta Sembiring (Majalah Ilmiah METHODA, 2017)
The purpose of this study is to explain the maintenance of the Karo language in Tiga Juhar. This study uses qualitative research, especially case studies. The subjects studied were 2 people; 1 is Christian and 1 is Muslim. Subjects were chosen specifically because they had to meet the criteria for having children, being able to speak their own tribal language fluently. Data were obtained by using interviews and observation. The data analysis technique used the Miles and Huberman method, namely data reduction, data classification, verification, and conclusion. In data analysis, it was found that a. Four factors that influence language defense are attitude, values and identity factors, social factors, religious factors, and demographic factors. b. There are two ways to maintain the language, namely creating an environment that integrates the use of regional languages and the continuous use of regional languages.